Analysis of the quality of work life in the Brazilian telecommunications sector - Agostinho, Oswaldo Luiz; Pinto, Jefferson de Souza; Gibbin, Randal Victor (Brazilian Journal of Production Engineering, 2021)
Context: Quality of Work Life (QWL) has assumed a prominent place in recent years as a component of organizational culture, being one of the pillars of sustainability. Objective: Identify how the four largest telecommunications groups operating in Brazil understand QWL in this context (two of which listed in the ISEB3/2020 portfolio). Method: A lexical analysis was carried out, processed by the IRAMUTEQ software, of the sustainability documentation available in the public repositories of these organizations, deployed in the Lexicographic Analysis, Descending Hierarchical Classification and Similitude Analysis. Results: The results show a prevalence of practices related to occupational health, training, development, and volunteering. Conclusion: Opportunities for improvement are verified in issues related to stress reduction, mentoring, conflict resolution, awards, and recognition. This research has its originality in the use of the textual analysis technique to the object of study